A magnetic levitated vertical axis wind turbine II - Goo, Chee Tiong. (2010)
The popularity of renewable energy has experienced a significant upsurge in recent times due to the exhaustion of conventional power generation methods and increasing realization of its adverse effects on the environment. The objective of this project is the creation of small scale magnetic levitating vertical axis wind turbine. The reason for choosing the Inductrack method as the levitation technique is because of its passive magnetic levitation nature which is of lower energy input comparing to other Maglev techniques. The basic explanation of the Inductrack method for magnetic levitation is given. The overall system is explained by design equations, simulations, fabrication, testing methods, and results. Propulsion methods are not covered as the concept is used on vertical axis wind turbine. The conclusion includes a summary, possible applications, and suggestions for further development of the project.